Pseudoaneurysm of the ascending aorta after aortic valve replacement - Osvaldo Valdés Dupeyrón; Geraldo Céspedes Arias; Boris Mederos Osorio; Pedro Pupo Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Postsurgical pseudoaneurysms of the ascending aorta are a rare and serious complication of cardiovascular surgery that requires a surgical solution of urgency due to its high complexity. A case of a 40 year old female, white skin color, that due to severe aortic regurgitation underwent surgical treatment for aortic valve replacement. During the immediate postoperative period began with a fever, he made a meticulous study that included contrast computed tomography, through which diagnosed the presence of a pseudoaneurysm of the ascending aorta, was taken to the operating room, they found two sacks pseudoaneurismatics at the site where the suture was carried out previous.